The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.5751/es-08515-210246
|View full text |Cite
|
Sign up to set email alerts
|

Perpetual private land conservation: the case for outdoor recreation and functional leisure

Abstract: ABSTRACT. As natural areas, agricultural lands, and open spaces continue to be developed at unprecedented rates, it is important for land conservation professionals to understand the individuals who might play a role in permanently protecting these lands and their ecological services. Many factors have been shown to influence land protection decisions among private owners, including land-use activities, demographic characteristics, and environmental intention and behavior. With the hypothesis that individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…We found that PCA ownership was neither purely philanthropic nor purely self‐interested; it also provided an opportunity to engage in functional leisure activity that is both enjoyable and productive (Farmer et al. ). For landowners, a PCA was a constitutive element of a happy and virtuous life: a project that achieves well‐being through “well‐doing” (Ryan ; Little ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that PCA ownership was neither purely philanthropic nor purely self‐interested; it also provided an opportunity to engage in functional leisure activity that is both enjoyable and productive (Farmer et al. ). For landowners, a PCA was a constitutive element of a happy and virtuous life: a project that achieves well‐being through “well‐doing” (Ryan ; Little ).…”
Section: Discussionmentioning
confidence: 99%
“…While these can be in response to external incentives and drivers (see Section 3), experience and research (e.g. Farmer et al, 2011;Leménager et al, 2014;Selinske et al, 2015;Farmer et al, 2016) indicate that for many individuals the most powerful motivations are personal and intrinsic, ranging from altruism to spiritual or religious beliefs, and are often complicated. Mechanisms for the recognition and establishment of PPAs vary depending on a country's legal and regulatory frameworks (or lack of them) (Mitchell 2005).…”
Section: Best Practicesmentioning
confidence: 99%
“…However, it would be wrong to conclude that land conservation is an entirely economic decision. Many studies have shown that landholders' primary motivations are not economic but intrinsic, with incentives making it possible to act on a sense of stewardship (see Principle 3.4) (for example, Farmer et al, 2016). As stated by landowner George Leonhard on why he and his brother protected their farm with a conservation easement granted to Greenbelt, "I could not bear to look at the property with houses all over it.…”
Section: Ppas Across the Usamentioning
confidence: 99%
“…The trade-offs between recreation and conservation pose a problem for conservation organizations and natural resource managers, given participation in outdoor recreation has been linked to interest in conservation easements (Farmer, Brenner, Drescher, Dickinson, & Knackmuhs, 2016), financial contributions to conservation organizations (Zaradic, Pergams, & Kareiva, 2009), and pro-conservation behaviors (Cooper et al, 2015). Despite variability in animal responses to recreation and remaining knowledge gaps, we believe our findings underline the importance of managing recreation on conservation lands.…”
Section: Discussionmentioning
confidence: 74%
“…Despite variability in animal responses to recreation and remaining knowledge gaps, we believe our findings underline the importance of managing recreation on conservation lands. The trade-offs between recreation and conservation pose a problem for conservation organizations and natural resource managers, given participation in outdoor recreation has been linked to interest in conservation easements (Farmer, Brenner, Drescher, Dickinson, & Knackmuhs, 2016), financial contributions to conservation organizations (Zaradic, Pergams, & Kareiva, 2009), and pro-conservation behaviors (Cooper et al, 2015). Funding sources for land acquisition (e.g., the U.S. Land and Water Conservation Fund) often mandate public access, limiting managers' ability to restrict recreation for conservation objectives.…”
Section: Discussionmentioning
confidence: 99%